Choline phosphate functionalized surface: protein-resistant but cell-adhesive zwitterionic surface potential for tissue engineering. Issue 3 (19th November 2014) - Chen, Xingyu; Chen, Tianchan; Lin, Zaifu; Li, Xian'e; Wu, Wei; Li, Jianshu
Abstract : A choline phosphate (CP) modified zwitterionic surface is prepared with both protein-resistant and cell-adhesive properties, exhibiting great potential for biomedical applications such as tissue engineering. Abstract : A choline phosphate (CP) modified surface is designed to resist protein adsorption due to its zwitterionic properties and simultaneously promote cell adhesion though its universal interaction with phosphate choline (PC) headgroups of the cell membrane. This work provides a new approach to obtain a cell-adhesive surface with a non-biofouling 'background', which has a potential for tissue engineering.